Financial Controls, an Old Function in a New Role - Vigvári, András (Theory, Methodology, Practice – Review of Business and Management, 2005)
The phenomenon of financial controls is as old as money. The ancient rulers wanted to know if their subordinates gave an accurate report on how the tax revenues was spent. Traders in Lombardy wanted to be ensured that their employees had not cheated. The owners of joint stock companies are also curious whether the board that leads the company and the managers act in the owners' interest when managing the company. I believe that the appearance and consolidation of the financial system, which is without internal values and based on trust, and the increasing need for financial stability have given increasing role to financial controls. The global financial crises in the third part of the 1990's has resulted a new situation in the operation of the international financial system. It has been pointed out that financial stability can only be guaranteed by global regulation and control, supervision and audit. Financial controls have been put in a new position qualitatively due to the development of the uniformed controlling procedures and the internationally co-ordinated operation of institutions. It cannot be ruled out that financial controls will be the generator and creator of global co-ordination. This article tries to discuss the arguments of this hypothesis as well as present some data supporting it.